Substantiation of the Absolute Velocity of the Soil Thrown by a Spherical Disc of the Roller of a Ridge Roller Planter - Zykin Evgeny (EDP Sciences, 2021)
For the finishing operation of the formation of the soil ridge of the required parameters and density simultaneously with sowing, a tillage roller has been designed, the novelty of which is confirmed by the patents of the Russian Federation No. 194330, No. 194348, No. 196712. The design of the roller assumes the regulation of the attack angles of the spherical discs and the amount of compression of the spring, because these parameters have a significant impact on the geometric dimensions of the formed ridge and the density of the soil in it. The proposed roller is mounted on the rear bead holder of a sowing gang of the ridgeroller planter. Moving along the surface of the field, the coulters of the ridge roller planter sow seeds on a wet compacted bed, the ridge formers form a loose soil ridge above the sown seeds, and the rollers compact the soil ridge. The speeds and forces acting on the spherical disc of the roller have been determined. It has been theoretically revealed that the absolute velocity of soil particles thrown by the edge of a spherical disc towards the longitudinal axis of symmetry of the soil ridge is maximum and depends on the angular speed of the spherical disc, its radius and angle of attack, as well as the frictional properties of the soil. The absolute speed of soil particles thrown from a specific point of the considered working body of the roller decreases when they approach the center of the spherical disc.